PKM KERAJINAN “BALI GOOD” PATUNG LIMBAH PANTAI DI DESA BLAHBATUH KABUPATEN GIANYAR - Putu Yudha Asteria Putri; I Gusti Ayu Ratih Permata Dewi; I Gede Nyoman Carlos W Mada (Universitas Kadiri, 2020)
ABSTRACTThe management of